Faktor Risiko yang Behubungan dengan Swamedikasi Demam pada Anak di Desa Lubuk Empelas Kecamatan Muara Enim, Privinsi Sumatera Selatan - Fedora Jolie Jolie; Djap Hadi Susanto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Self-medication is a community action in overcoming symptoms of the disease by using over-the-counter drugs without going to a doctor. Self-medication by the community is generally obtained from generation to generation from previous experience. Symptoms of illness that are treated, generally are fever. The study aims to determine the factors associated with self-medication for fever in children. The research method used is a cross-sectional approach, data were collected using a questionnaire obtained by interviewing and filling out a questionnaire. Subjects are children aged 1-12 years, questionnaire to the child’s mother. Data were analyzed using univariate and bivariate. Results: The proportion of fever self-medication behavior was 69%. The average education level of high school graduates, and family income is below the regional minimum wage. The majority of children were in the range of 5-9 years. Self-medicated by their mothers with fever due to common illnesses such as colds. There was a relationship between the mother's level of knowledge (p = 0.000), information sources (p = 0.044), and the number of children (p = 0.027) with fever self-medication behavior in their children.